Influenza vaccine coverage in 6months-64 years-old patients affected by chronic diseases: A retrospective cohort study in Italy - Francesco Paolo Bianchi; Pasquale Stefanizzi; Eustachio Cuscianna; Antonio Di Lorenzo; Giovanni Migliore; Silvio Tafuri; Cinzia Annatea Germinario (Taylor & Francis Group, 2023)
At the beginning of each flu season, the Italian Ministry of Health defines the categories at higher risk of influenza complications, for which vaccination is actively and freely offered. The vaccine coverage (VC) of the influenza vaccine in subjects from 6 months to 64 years of age suffering from diseases that increase the risk of complications from influenza during the 2020-2021 season was evaluated. Our study wants to evaluate the VCs of the influenza vaccine in these subjects during the 2020/2021 season in Apulia. The digital archives relative to the Apulian population were used. A retrospective cohort study design was performed. 484,636 Apulian residents aged between 6 months and 64 years suffered from at least one chronic disease; 139,222 of 484,636 subjects received the influenza vaccine (VC: 28.7%) from October 2020 to January 2021. Considering the single comorbidities, the greatest values are found for pathologies for which major surgical interventions are planned and chronic renal failure/adrenal insufficiency patients, while the worst for chronic liver diseases and pathologies for which major surgical interventions are planned. In any case, it would seem that better VC is achieved in subjects with more than one chronic condition. Influenza vaccination must be promoted as a central public health measure, also because by reducing the burden on hospitals, it can greatly benefit the management of COVID-19 patients. Greater efforts by public health institutions must be implemented in order to achieve better VC in the target categories, including chronic patients.